Keberkahan Mandi Safar: Menelusuri Spiritualitas dan Tradisi Masyarakat Muna - Ode, Nur Indah; Aris, La Ode (JURNAL KABANTI: Kerabat Antropologi, 2025)
The Mandi Safar ritual of the Muna people in Wakumoro Village, Parigi District, is a tradition that is full of meaning and function in the social and spiritual life of the community. This study aims to describe the implementation process and explore the function of the Mandi Safar ritual in the context of local beliefs and culture. The method used is qualitative research with data collection techniques through in-depth interviews and participatory observation of community members involved in the ritual. The results of the study show that the Mandi Safar Ritual is held every year in the month of Safar, especially on the last Wednesday. The implementation process includes a pilgrimage to the tomb of King Muna La Ode Dika, preparation of ritual materials, and reading prayers called baca-baca Haroa. This ritual has three main functions: as a ward off disaster, increasing agricultural yields, and as a medium for healing diseases. The Mandi Safar Ritual not only plays a role in respecting tradition, but also becomes a means to strengthen social ties and the identity of the Muna community. This study implies the importance of preserving this ritual as part of the cultural heritage and local wisdom that can strengthen the character of society amidst changing times.